Body sweats : the uncensored writings of Elsa von Freytag-Loringhoven - Freytag-Loringhoven, Elsa von, 1874-1927 (MIT Press, 2011)
This is a collection of poetry written in English by the flabbergasting and flamboyant Baroness Elsa, 'the first American Dada'. Many of the poems are themselves art objects, decorated in red and green ink, adorned with sketches and diagrams.